The interdependence of innovation and investment potential of the regions - E. F. Nikitskaya; M. A. Valishvili (Путеводитель предпринимателя, 2020)
The article discusses a meaningful balance of economic categories «innovation potential» and «investment potential» in the conditions of transition to innovative model of development. The authors proved that with the expansion in the structure of the national economy innovative component of the inevitable transformation of approaches to the investment potential and investment policy at the regional level.